2013
DOI: 10.1111/syen.12001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of diversification in the high Andean Ponderacris grasshoppers (Orthoptera: Acrididae: Melanoplinae)

Abstract: The Andes, the world's longest mountain chain, harbours great taxonomic and ecological diversity. Despite their young age, the tropical Andes are highly diverse due to recent geological uplift. Speciation either followed the orogeny closely or occurred after the Andean uplift, as a result of subsequent climatic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
(56 reference statements)
1
12
0
7
Order By: Relevance
“…Fourteen biogeographical provinces, regions containing high levels of biodiversity and endemism, are currently recognized as part of the Andes in the South American transition zone and the Andean region sensu Morrone (, ). Andean uplift was suggested as a driver of diversification in taxa such as the angiosperm genera Heliotropium L. (Luebert et al ., ) and Hedyosmum Sw. (Antonelli & Sanmartín, ), scorpions (Mattoni et al ., ), grasshoppers (Pocco et al ., ), glassfrogs (Hutter et al ., ), and brush‐finches (Sanchez‐Gonzalez et al ., ). Furthermore, Andean orogeny caused the separation of habitats and subsequent speciation of their respective faunas, especially in freshwater fishes (Albert et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen biogeographical provinces, regions containing high levels of biodiversity and endemism, are currently recognized as part of the Andes in the South American transition zone and the Andean region sensu Morrone (, ). Andean uplift was suggested as a driver of diversification in taxa such as the angiosperm genera Heliotropium L. (Luebert et al ., ) and Hedyosmum Sw. (Antonelli & Sanmartín, ), scorpions (Mattoni et al ., ), grasshoppers (Pocco et al ., ), glassfrogs (Hutter et al ., ), and brush‐finches (Sanchez‐Gonzalez et al ., ). Furthermore, Andean orogeny caused the separation of habitats and subsequent speciation of their respective faunas, especially in freshwater fishes (Albert et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…All species, except P. virescens, have a very restricted distribution, which could be an indicator of a probable widespread ancestor with broader distribution and speciation may have occurred due to the isolation of species on each mountain. There are other mountain melanoplines with similar patterns in genera, such as Jivarus (Cigliano and Amédégnato, 2010), Melanoplus (Knowles and Massatti, 2017), Orotettix (Scattolini et al 2018), and Ponderacris (Pocco et al 2013) among others. Mastretta-Yanes et al (2015) analyzed high-elevation taxa in the TransMexican Volcanic Belt and found that these taxa have been exposed to a sky-island dynamic due to climate variations.…”
Section: Discussionmentioning
confidence: 90%
“…Even though the Chaco biome has been surveyed by outstanding acridiologists (Liebermann J., Carbonell C.S., Ronderos R.A., among others) rendering a significant knowledge of its acridiofauna, at least for some groups such as romaleids, it seems that there are still undiscovered species in the region. We emphasize the importance of systematic surveys of this highly diversified biome of South America that may not only render the discovery of new species, but also contribute to a better knowledge of species richness and endemism, as a path leading to improved conservation strategies (Pocco et al ., ).…”
Section: Discussionmentioning
confidence: 97%